GROUNDING MORAL MODERATION IN ADDRESSING THE EROSION OF SOCIAL VALUES - Arif Sugitanata; Akmal Bashori; Afriadi Putra; Supriyadi; Muhammad Hasyied Abdurrasyied (UIN Antasari Banjarmasin, 2024)
This article examines the phenomenon of moral erosion in modern society, influenced by globalization, technological advancements, and demographic changes, which contribute to the rise of crime, corruption, and the degradation of social trust. Employing a qualitative research approach based on the theory of Maqāṣid al-sharīʿah and a literature review, this study proposes moral moderation as a crucial strategy for restoring and strengthening social values, particularly in multicultural societies. The findings reveal that moral erosion is marked by a decline in the application of social norms, driven by factors such as globalization and economic disparities, which complicate the integration of values within society. Moral moderation is proposed as a response to balance behavior and prevent extremism, and it is essential in cultivating wise and responsible character. This concept is also relevant in educational and workplace settings, supporting the principles of Maqāṣid al-sharīʿah in safeguarding vital human aspects. The article also explores the relationship between moral moderation and religious moderation in Indonesia, emphasizing the importance of balance and respect for diversity to create a harmonious and tolerant society. This research provides academic contributions and practical recommendations for policymakers and educators to strengthen morality in modern society.